The LME project: legislative metadata based on semantic formal models. (11th August 2009) - Bartalesi Lenzi, Valentina; Biagioli, Carlo; Cappelli, Amedeo; Sprugnoli, Rachele; , Fabrizio Turchi
The Law Making Environment (LME) system for planning, drafting and managing legislative sources is made up of editing and search support tools. To handle the semantics of legislative sources, two interacting models have been created: a rule model, which can describe the illocutionary profile of legislative texts through metadata, and a lightweight ontology. The search support tool, LMEmetaSearch, based on both models, is able to search for rules in legislative sources, and additionally to find implicit or complementary rules providing the user with a wide account on the subject.